Continuing education to combat domestic and gender-based violence: an experience report - Maria Fernanda Terra; Rosa Maria Godoy Serpa da Fonseca (Revista Brasileira de Enfermagem)
ABSTRACT Objectives: to report the implementation of supervision for healthcare professionals from Violence Prevention Centers in healthcare services in two regions of the city of São Paulo, Brazil. Methods: an experience report of planning and executing supervision meetings from the perspective of critical-emancipatory education. Results: twenty meetings were held with critical reflections on domestic and gender-based violence as a barrier to continuity of life and the need to make the phenomenon visible and take it into account when planning healthcare. Final Considerations: the experience offers a practical perspective on supervising health workers that is consistent with maintaining ongoing education and health surveillance to improve the way domestic and gender-based violence is addressed in healthcare services.